POROGEN EFFECT TOWARDS THE QUALITY OF CURCUMIN IMPRINTED POLYMER - Emi Shaqiza Azizi; Mohd Noor Ahmad; A.K.M. Shafiqul Islam; Dahyar Arbain; Iqmal Tahir (Indonesian Journal of Chemistry, 2011)
Molecularly imprinted polymer (MIP) is gaining importance in separation technology. In this study, curcumin has been selected as template in MIP which can be applied as sorbent materials in solid-phase extraction (SPE). Effect of porogen on the quality of curcumin-MIP is very sensitive depends on the molecular size and polarity of the porogen. We varied three solvents as the porogen i.e. tetrahydrofuran (THF), chloroform (CHCl3) and acetonitrile (MeCN). The MIP was prepared using non-covalent approach through bulk polymerization and non-imprinted polymer (NIP) as control, also prepared using the same procedure in the absence of template. The largest imprinting factor, 1.27 was obtained from polymer P1 at ratio 1:4 of template: functional monomer. The P1 was prepared using methacrylic acid (MAA) as functional monomer and tetrahydrofuran (THF) as porogen with the highest average pore diameter i.e. 618.43 nm trough gas adsorption analysis. This will lead to better access of curcumin during batch binding analysis.